Boss's baby acquisition - Anderson, Natalie, 1973- (Anderson, Natalie, 1973- Convenient wives club, 2025)
"PA Phoebe Copeland was married once -- never again. But a steamy vacation encounter with a stranger she'll never see again? More than fine! Until he walks into her London boardroom ... He's billionaire Edoardo Benedetti -- and he's bought the company she works for! Edoardo has mastered the art of separating the personal from the professional. Except his intense awareness of Phoebe pushes him to the brink of distraction. Then he's brought down to earth with a bump: Phoebe's pregnant! As her boss, he could contain their chemistry. Now she's carrying his heir, all bets are off!" --